Dynamical systems - Sternberg, Shlomo (Mineola, N.Y. : Dover Publications, 2010)
"Celebrated mathematician Shlomo Sternberg, a pioneer in the field of dynamical systems, created this modern one-semester introduction to the subject for his classes at Harvard University. Its wide-ranging treatment covers one-dimensional dynamics, differential equations, random walks, iterated function systems, symbolic dynamics, and Markov chains. Supplementary materials offer a variety of online components, including PowerPoint lecture slides for professors and MATLAB exercises."--Publisher's description.
Iteration and fixed points -- Bifurcations -- Sarkovsky's theorem, Singer's theorem, intermittency -- Conjugacy -- Space and time averages -- The contraction fixed point theorem -- The Hausdorff metric and Hutchinson's theorem -- Hyperbolicity -- The Perron-Frobenius theorem -- Some topics in ordinary differential equations -- Lotka-Volterra -- Symbolic dynamics.
Includes bibliographical references (p. 261-265) and index.
Keywords: Dynamics; Differentiable dynamical systems